Early Holocene ritual complexity in South America: the archaeological record of Lapa do Santo (east-central Brazil). (21st November 2016) - Strauss, André; Oliveira, Rodrigo Elias; Villagran, Ximena S.; Bernardo, Danilo V.; Salazar-García, Domingo C.; Bissaro, Marcos César; Pugliese, Francisco; Hermenegildo, Tiago; Santos, Rafael; Barioni, Alberto; de Oliveira, Emiliano Castro; Moreno de Sousa, João Carlos; et al.
Abstract: Abstract : Early Archaic human skeletal remains found in a burial context in Lapa do Santo in east-central Brazil provide a rare glimpse into the lives of hunter-gatherer communities in South America, including their rituals for dealing with the dead. These included the reduction of the body by means of mutilation, defleshing, tooth removal, exposure to fire and possibly cannibalism, followed by the secondary burial of the remains according to strict rules. In a later period, pits were filled with disarticulated bones of a single individual without signs of body manipulation, demonstrating that the region was inhabited by dynamic groups in constant transformation over a period of centuries.